Structure of the cel-3 gene from Fibrobacter succinogenes S85 and characteristics of the encoded gene product, endoglucanase 3. - McGavin, M J (1989)
The cel-3 gene cloned from Fibrobacter succinogenes into Escherichia coli coded for the enzyme EG3, which exhibited both endoglucanase and cellobiosidase activities. The gene had an open reading frame of 1,974 base pairs, coding for a protein of 73.4 kilodaltons (kDa). However, the enzyme purified from the osmotic shock fluid of E. coli was 43 kDa. The amino terminus of the 43-kDa protein matched amino acid residue 266 of the protein coded for by the open reading frame, indicating proteolysis in E. coli. In addition to the 43-kDa protein, Western immunoblotting revealed a 94-kDa membranous form of the enzyme in E. coli and a single protein of 118 kDa in F. succinogenes. Thus, the purified protein appears to be a proteolytic degradation product of a native protein which was 94 kDa in E. coli and 118 kDa in F. succinogenes. The discrepancy between the molecular weight expected on the basis of the DNA sequence and the in vivo form may be due to anomalous migration during electrophoresis, to glycosylation of the native enzyme, or to fatty acyl substitution at the N terminus. One of two putative signal peptide cleavage sites bore a strong resemblance to known lipoprotein leader sequences. The purified 43-kDa peptide exhibited a high Km (53 mg/ml) for carboxymethyl cellulose but a low Km (3 to 4 mg/ml) for lichenan and barley beta-glucan. The enzyme hydrolyzed amorphous cellulose, and cellobiose and cellotriose were the major products of hydrolysis. Cellotriose, but not cellobiose, was cleaved by the enzyme. EG3 exhibited significant amino acid sequence homology with endoglucanase CelC from Clostridium thermocellum, and as with both CelA and CelC of C. thermocellum, it had a putative active site which could be aligned with the active site of hen egg white lysozyme at the highly conserved amino acid residues Asn-44 and Asp-52.